Spore loses two stalwarts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Two long-serving and deeply-committed members of the team which oversees the production of Spore have recently left CTA.They are Dominique Hounkonnou, an agricultural engineer with a background in French-speaking West Africa, and JoyMukanyange, an...